EFEKTIVITAS METODE JARIMATIKA TERHADAP MOTIVASI BELAJAR SISWA KELAS V DI SEKOLAH DASAR ISLAM ALBAYYINAH MAKASSAR PADA MATERI PERKALIAN PECAHAN - A.St.Syarifah Fatimah; Widya Karmila Sari Achmad; Faidah Yusuf (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The aim was to determine the effectiveness of the Jarimatika method on fifth-grade students’ learning motivation in fraction multiplication at Al Bayyinah Islamic Elementary School Makassar. A total of 50 students were selected as samples through cluster random sampling. Data were collected through tests, teacher and student observations, and learning motivation questionnaires, then analyzed using descriptive and inferential statistics. The results showed that the Jarimatika method was implemented very well and significantly increased students’ learning motivation (sig. 0.000 < 0.05), particularly in the aspect of learning interest. Therefore, the Jarimatika method is effective in enhancing students' motivation to learn, especially in learning mathematics on the topic of fraction multiplication.